Estimation of mean ND: Yag laser capsulotomy energy levels for membranous and fibrous posterior capsular opacification - Bhargava, R; Kumar, P; Prakash, A; Chaudhary, KP (Nepalese Journal of Ophthalmology, 2012)
Introduction: Posterior capsule opacification (PCO) is a visually-disabling complication of cataract surgery. Objective: To estimate energy levels for capsulotomy in various subtypes of PCO (membranous, fibrous and fibro-membranous). Materials and methods: A total of 215 patients with PCO were randomly selected and evaluated for Nd: Yag laser capsulotomy, after a quiet post-operative course of 3 months. The ocular area was arbitrarily divided into three zones: YAG zone (3mm), Optical zone (6 mm) and the peripheral zone (12mm). A colour code was assigned to the subtype of PCO in these zones: fibrous green and membranous blue. The type of PCO in each quadrant of YAG zone was estimated in percentage. Results: The statistic mean values of initial energy levels were 1.80 mJ for membranous PCO, 3.17 mJ for fibrous PCO and 2.73 mJ for fibro-membranous PCO. The mean summated energy levels for membranous PCO was 22.80 mJ for membranous PCO, 80.06 mJ for fibrous PCO and 80.48 mJ for fibro-membranous type. Conclusion: Colour coding is extremely helpful for quantification of the type of PCO and in deciding the initial energy level necessary to create capsulotomy. Fibro-membranous PCO required more summated energy despite a lower starting energy. Therefore, we recommend firing the initial shot in fibrous portion in case of fibrous-membranous type of PCO. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5861 NEPJOPH 2012; 4(1): 108-113